О таксономических взаимоотношениях Parus major intermedius (Zarudny) с синицами смежных регионов - Мищенко, Ю.В. (Вестник зоологии, 1982)
The relations of Parus major intermedius(Zar.) with tits of adjoiningareasare considered with special reference to morphological characters, habitats and distribution patterns. P. m.intermediusi ssuggested to befar closer to the nominate subspecies than to P. cinereus Vieill. and P. bokharensis Licht.; intermedius suggested to be a mar- ginalsubspecies o f P .major L. The differences of P. cinereus and P. bokharensis from P. major reach the species level. The recent absence of ring range overlappingin P. major and different evolution tempo in its different forms are established. Possible ways of recent interrelations of P. m. intermedius with other forms are discussed.